The first study of real-world efficacy and safety of Natalizumab (Tysabri®) in Iran - Amin Shahrbaf, Mohammad; Samimi, Monireh; Karimi, Shahedeh; Salari, Mehri; Ghaffari, Mehran; Yazdanbakhsh, Sepideh; Najafian, Abbas; Vosough, Massoud; Massood Nabavi, Seyed (Trends in Immunotherapy, 2024)
Objectives: Natalizumab is an injectable DMT (disease-modifying therapy) which used for RRMS (relapsing-remitting multiple sclerosis) since 2006. The drug has been available in Iran since 2014. Introduction: This study was aimed to evaluate the real-world effectiveness of Natalizumab in a referral center in Tehran, Iran. This study is the first real world analysis of efficacy and safety of Natalizumab in our country. Methods: In this retrospective study, patients with RRMS were investigated in a high-volume center in Tehran from 2019 to 2021. MS (Multiple Sclerosis) patients under treatment with Natalizumab who have received at least 3 infusions of the drug and had completed follow-up data, have been evaluated for safety and efficacy of Natalizumab. Results: 100 patients were included in the final analysis. The mean follow-up time was 20 months (6–33 months). The median EDSS (Expanded Disability Status Scale) score of patients reached to 2 from 2.5 after the treatment course (P < 0.0001). The annualized relapse rate (ARR) decreased from 0.81 (95% CI: 0.73–0.87) to 0.023 (95% CI 0.009–0.061). The median JCV (John Cunningham virus) index remained unchanged before treatment 0.85 (IQR: 0.21–2.41) compare to after the treatment 0.85 (IQR: 0.21–2.31). The number of patients with active brain and cervical MRI (Magnetic Resonance Imaging) lesions decreased significantly (P = 0.001). NEDA-3 (No evidence of disease activity) was improved from 9% to 87% after the treatment with Natalizumab. No serious adverse events except than one progressive multifocal encephalopathy (PML) case have been found. The main reasons of switching from Natalizumab to the other DMDs (Disease Modifying Drugs) were positive JC index, starting phase, noncompliance, pregnancy, MRI activity and seroconversion after starting the drug. Conclusion: Natalizumab is a safe and effective choice in RRMS patients for reducing relapse rate, disability score, active MRI lesion, and improving the NEDA (No evidence of disease activity).